Penyuluhan Tentang Kontrasepsi Pasca Persalinan (IUD dan Implant) di Puskesmas Batua Raya Makassar - Rismawati Rismawati; Andi Fatimah Jamir (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2022)
Indonesia is a country that is seen from its population in the fourth position in the world, with a relatively high growth rate. The essence of the task of the Family Planning (KB) program in this case is clear, namely reducing fertility in order to reduce the burden of development for the realization of happiness and prosperity for the people and nation of Indonesia. As stated in Law No. 10 of 1992 concerning Population Development and Development of Prosperous Families, the definition of family planning is an effort to increase awareness and community participation through maturing the age of marriage, birth control, fostering family resilience, and increasing family welfare in order to create a small, happy family. and prosperous. Contraceptives are very useful in family planning programs, but it should be noted that not all contraceptives are suitable for everyone's condition. Contraceptive services (PK) is one type of family planning services available. Most family planning acceptors choose and pay for the various methods of contraception available. This counseling is carried out because it is based on the profession of midwives as health workers who provide services and education about the use of contraception so that extension workers are interested in providing counseling about the choice of contraception after childbirth.